Øen i den keltiske verdensopfattelse - Warmind, Morten Lund (Religionsvidenskabeligt Tidsskrift, 1996)
It is well known that the Celts oriented their physical environment around a centre as can be seen from a number of Continental place-names. In Ireland we even find a highly developed division of the island according to the four corners of the world into four "provinces" around the centre. The division is ideological or religious rather than political. It is argued that this division of the world included an island outside of the sphere of the ordered world, from which it was thought that knowledge - especially druidical knowledge - originated. This again throws light on the famous remark by Julius Caesar that druidry had its origin in Britain. To the Continental Gauls, who were Caesar’s informants, Britain was "The Island Across The Sea", whereas this island in Britain may have been Ireland as in the tales of Mona (Modern Anglesey) in historical fact. It is speculated that the islands in fact as well as in myths were thought to be religiously important. Several examples of islands as centres of magical knowledge from Celtic literature are given concluding with the role of Land og Magic given to Ireland in the Tristan-poems.